Comparison of the expression of PI3K/AKT pathway components in type 2 diabetic and non- diabetic human volunteers ex vivo - Khorami, Somayeh Alsadat Hosseini (2018)
Insulin resistance in T2DM has been characterized by several defects in insulin signalling. Insulin-stimulated glucose transport occurs via PI3K/AKT-dependent pathway which results in GLUT4 translocation from intracellular vesicles to the plasma membrane and increased glucose uptake. Upon stimulation of insulin, PI3K phosphorylates membrane phospholipids and converts PIP2 to PIP3. This complex phosphorylates/activates PDK1 leading to activation of AKT and co- localization at plasma membrane. PTEN phosphatase antagonizes PI3K/AKT signalling by converting PIP3 to PIP2. Overexpression of PTEN in T2DM, results in inhibition of AKT signalling pathway and GLUT4 translocation. The present cross-sectional study was performed to investigate the underlying transcription level of gene of interest in insulin signalling mechanism responsible for these defects based on the characterization of socio-demographic, biochemical properties, serum vitamin D and calcium level. Hence, real time-PCR was employed in this study to investigate the interaction on the gene of interest (GOIs) such as IRS1, PI3K, PDK1, AKT2, GLUT4, GSK3 and PTEN of fifty non-diabetic and fifty T2DM respondents. Findings provide evidence that the gene expression level of IRS and GSK3 was preserved while PI3K, AKT2, PDK1 and GLUT4 were expressed significantly (P < 0.05) lower in T2DM respondents compared to non- diabetic respondents. Glucose levels (HbA1c and FBS), lipid profiles (TC, TG, LDL and HDL) were tested by colorimetric enzymatic method, serum vitamin D and calcium were measured by HPLC and C-peptide levels were determined by ELISA. Glucose levels (HbA1c and FBS) in diabetic were significantly higher (P < 0.05) compared to non-diabetic respondents and C-Peptide did not show any significant difference. The average level of TC was found to be significantly higher in diabetic respondents and LDL was significantly lower in diabetic respondents compared to non-diabetic. Current study indicates, only PTEN expression level had a significant relation with duration of diabetes. This finding suggests that PTEN may not be the cause of the reduced gene expression level of PI3K/AKT pathway in Type II diabetes. As the findings of the present study showed reduced gene expression level of PI3K, PDK, AKT2, GLUT4 in diabetic respondents compared to non-diabetic respondents, therefore, the impaired gene expression of PI3K/AKT pathway may play a primary role in the pathogenesis of the disease while PTEN is not the primary cause and it is up-regulated by the years of having diabetes.